Challenges for application of realgar: A critical review - Vineet Sharma; Narendra Kumar Singh; Dev Nath Singh Gautam (Wolters Kluwer Medknow Publications, 2016)
Realgar has been not only well-known poisons but also used as healing agent. Realgar has long been used in traditional medicines for different diseases; so far arsenic can be extremely toxic and carcinogenic. In Ayurvedic and Chinese traditional medicines arsenic usually comes from conscious addition for healing purposes, mostly in the form of mineral arsenicals with orpiment (As2S3), realgar (As4S4), and arsenic trioxide (As2O3). Pharmacological studies revealed that realgar is effective against in different cancer cell line. However, it has been critically limited clinical applications because of its many disadvantages, for example, low solubility in water, high toxicity, poor gastrointestinal absorption, and bioavailability. This review evaluates the toxicology, bioaccessibility, and pharmacology of the realgar used in Ayurvedic and Chinese traditional medicines. In recent times, numerous types of realgar nanoparticles (NPs) have been developed due to insolubility of realgar in water and different media. Most of the NPs of realgar possess the exclusive optical qualities of quantum dots. The pharmacological activities and bioavailability of realgar NPs are much more partial by their sizes, building realgar an exciting biomedical and pharmaceutical research applicant.